2021
DOI: 10.1016/j.medj.2021.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Maternal respiratory SARS-CoV-2 infection in pregnancy is associated with a robust inflammatory response at the maternal-fetal interface

Abstract: Background Pregnant women are at increased risk for severe outcomes from coronavirus disease 2019 (COVID-19), but the pathophysiology underlying this increased morbidity and its potential effect on the developing fetus is not well understood. Methods We assessed placental histology, ACE2 expression, and viral and immune dynamics at the term placenta in pregnant women with and without respiratory severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
171
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(202 citation statements)
references
References 111 publications
19
171
0
12
Order By: Relevance
“…The researchers found that these cells could be the targets of SARS-CoV-2 entry (96). Moreover, robust immune responses at the maternal-fetal interface of SARS-CoV-2-infected women was discovered (97).…”
Section: Biomarkers Of Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that these cells could be the targets of SARS-CoV-2 entry (96). Moreover, robust immune responses at the maternal-fetal interface of SARS-CoV-2-infected women was discovered (97).…”
Section: Biomarkers Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Researchers found overexpression of interferon-related genes, and increased activation of NK cells and T cells (97)(98)(99). Also, it was found that there was an association between SARS-CoV-2 infection and local immune responses at the maternal-fetal interface (97). in a study by Nagy et al, the impact of mutations in SARS-CoV-2 viral genes on clinical outcomes was explored.…”
Section: Biomarkers Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…The staining intensity of the cytotrophoblast cells using RNAscope as well as antibody to the SARS-CoV-2 nucleocapsid protein was much greater than that of the overlying syncytiotrophoblast, and although it cannot be confirmed from this study, may represent higher levels of the viral mRNA and antigen within these cells. This observation is interesting following the recent report from Lu-Culligan et al [48] that cytotrophoblasts, in addition to trophoblast stem cells, rather than syncytiotrophoblast or Hofbauer cells, were the most vulnerable cells to direct SARS-CoV-2 infection in vitro using immortalized cell lines and primary isolated placental cells. The staining of cytotrophoblast in this placenta for SARS-CoV-2 was intermittent, with some cells staining positive and the adjacent cells remaining unstained.…”
Section: Discussionmentioning
confidence: 54%
“…Recent evidence has suggested that in contrast to 1st and 2nd trimester placentas, there is low expression of the ACE2 viral receptor on placental trophoblast cells during the later stages of pregnancy [46,47], potentially accounting for the relatively low rate of transplacental transmission that occurs with SARS-CoV-2. However, there are data suggesting that term placentas from pregnant women infected with SARS-CoV-2 have increased levels of the ACE2 protein [48]. In addition to the syncytiotrophoblast, small numbers of infected placentas have been found to demonstrate positive immunohistochemical staining for SARS-CoV-2 in other fetal-derived placental cells including Hofbauer cells and villous capillary endothelial cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility may be due to the tolerogenic environment generated during pregnancy. For example, in SARS CoV2 infection, there seems to be an increased activation of NK and T cell in the maternal-fetal interface, despite the absence of virus in the tissue [77]. This effect may be due to inflammatory cytokines generated upon viral infection.…”
Section: Nk Cells In Infectious Diseases In Pregnancymentioning
confidence: 99%